Electroacupuncture plus moxibustion therapy for patients with major depressive disorder: study protocol for a randomized controlled trial. Issue 1 (December 2017) - Kim, Mikyung; Choi, Eun-Ji; Kim, Sung-Phil; Kim, Jung-Eun; Park, Hyo-Ju; Kim, Ae-Ran; Seo, Bok-Nam; Kwon, O-Jin; Cho, Jung; Chung, Sun-Yong; Kim, Joo-Hee
Abstract Background Major depressive disorder (MDD) is one of the most prevalent mental health disorders and has a significant societal economic burden. Antidepressants and cognitive behavioral therapy are two primary interventions for the standardized treatment of MDD. However, their weaknesses, such as a low response rate, a high risk of adverse events from medication, and the high cost of cognitive behavioral therapy, have resulted in a need for complementary and alternative medicine (CAM). Among the various therapeutic interventions in CAM, electroacupuncture and moxibustion have been widely used to treat various mental illnesses, including MDD. The aim of this study is to evaluate the feasibility of conducting a full-scale randomized controlled trial to investigate the efficacy and safety of electroacupuncture plus moxibustion therapy for MDD. Methods/design We will include patients between the ages of 19 to 65 years with MDD. A total of 30 participants will be recruited, and they will be randomly allocated into two groups at a 1:1 ratio. Patients in the treatment and control groups will, respectively, receive real and sham electroacupuncture/moxibustion treatments, for a total of 20 sessions over 8 weeks. The primary outcome will be the Hamilton Rating Scale for Depression, and the secondary outcomes will be Beck's Depression Inventory, the Insomnia Severity Index, the State-Trait Anxiety Inventory, the EuroQol 5-Dimension Index, the Measure Yourself Medical Outcome Profile version 2, and electroencephalography. Adverse events will be monitored at each visit to assess safety. All outcomes will be assessed and analyzed by researchers blinded to the treatment allocation. Discussion This is a two-armed, parallel-design, patient-assessor blinded, multicenter, randomized, sham-controlled pilot clinical trial. Data will be analyzed before and after treatment and during a 4-week follow-up. The results of the trial will provide a basis for further studies assessing the efficacy and safety of electroacupuncture plus moxibustion treatment for MDD. Trial registration Korean Clinical Trial Registry, CRIS-KCT0001810 . Registered on 5 February 2016 (retrospectively registered; date of enrollment of the first participant to the trial: 2 December 2015).